FLY ASH MAGNETIC ADSORBENT FOR CADMIUM ION REMOVAL FROM AN AQUEOUS SOLUTION - Gabriela BUEMA; Nicoleta LUPU; Horia CHIRIAC; Dumitru Daniel HEREA; Lidia FAVIER; Gabriela CIOBANU; Loredana FORMINTE (LITU); Maria HARJA (Journal of Applied Life Sciences and Environment)
The fly ash generated from a Romanian power plant was used as a starting material in this study. The aim of the study was to obtain a low cost material based on the treatment of fly ash with Fe3O4 for utilization as an adsorbent for cadmium ion removal. The adsorbent that was synthesized was characterized using different techniques. The adsorption process was investigated by the batch technique at room temperature. The quantity of cadmium ion adsorbed was measured spectrophotometrically. The experimental data showed that the material can remove cadmium ions at all three working concentrations. The adsorption capacity increased with an increase in concentration, respectively contact time. The results were analyzed through two kinetic models: pseudo first order and pseudo second order. The kinetics results of cadmium adsorption onto a magnetic material are in good agreement with a pseudo second order model, with a maximum adsorption capacity of 4.03 mg/g, 6.73 mg/g, and 9.65 mg/g. Additionally, the pseudo second order model was linearized into its four types. The results indicated that the material obtained show the ability to remove cadmium ions from an aqueous solution.